Computational simulation of fluid flow by using element based finite volume method on unstructured grids - Carlos Araujo; José Rincón; Gilberto Materano; Alejandro Colman (Revista Técnica de la Facultad de Ingeniería, 2010)
The results obtained in the development of the computational program “MEFVOC”, to simulate laminar incompressible and steady flows, using Element based Finite Volume Methods on unstructured and bidimensional grids, is presented in this paper. There are references to problems for testing and evaluating numerical techniques related with this method, but it is not common to find results on unstructured grids like the ones reached in this work. The implementacion makes easier the extention to complex geometries. The problems resolved demonstrate concordance with other authors, using structured grid. In fact, it can be concluded that the computational program developed, succesfully resolves the problems proposed under the described conditions.